2014
DOI: 10.1371/journal.pone.0084823
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Ligand Specificity of the Deleted in Colorectal Cancer (DCC) Receptor

Abstract: The growth and guidance of many axons in the developing nervous system require Netrin-mediated activation of Deleted in Colorectal Cancer (DCC) and other still unknown signaling cues. Commissural axon guidance defects are more severe in DCC mutant mice than Netrin-1 mutant mice, suggesting additional DCC activating signals besides Netrin-1 are involved in proper axon growth. Here we report that interaction screens on extracellular protein microarrays representing over 1,000 proteins uniquely identified Cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 41 publications
(60 reference statements)
3
46
2
1
Order By: Relevance
“…More importantly, we did not observe physical interactions between all tested pairs of zebrafish or human Draxin and Netrin receptors. These findings disagree with an earlier report (Ahmed et al, 2011) but agree with a recent study, which failed to detect a direct interaction between human Draxin and DCC using Surface Plasmon Resonance (SPR) (Haddick et al, 2014).…”
Section: Draxin Selectively Binds To G-netrinscontrasting
confidence: 76%
“…More importantly, we did not observe physical interactions between all tested pairs of zebrafish or human Draxin and Netrin receptors. These findings disagree with an earlier report (Ahmed et al, 2011) but agree with a recent study, which failed to detect a direct interaction between human Draxin and DCC using Surface Plasmon Resonance (SPR) (Haddick et al, 2014).…”
Section: Draxin Selectively Binds To G-netrinscontrasting
confidence: 76%
“…However, the role of Cbln4 is not so clear, as it does not bind to the same proteins at the synaptic cleft as Cbln1 does and it has no known role in the formation of synapses. In addition, Cbln4 null mice do not show an overt phenotype (Wei et al, 2012), although defects in axon path finding in development have been reported recently (Haddick et al, 2014). However, Cbln4 might be more important in adult life.…”
Section: Cerebellinmentioning
confidence: 98%
“…DCC was found to bind Cbln4 with high affinity (Haddick et al, 2014;Wei et al, 2012). Tentatively, Cbln4 produced and secreted by the postsynaptic pyramidal neurons would bind to DCC in incoming axons from the interneurons, thereby inducing a GABAergic differentiation and the maintenance of the GABAergic differentiated state.…”
Section: Cerebellinmentioning
confidence: 99%
“…Canonical receptors for netrin-1 in mammals include deleted in colorectal cancer (DCC), the DCC paralog neogenin, and the four UNC5 homologs, UNC5A-D, all of which are Ig superfamily, cell adhesion molecule (CAM)-like, type 1 transmembrane proteins (Lai Wing Sun et al 2011). In addition to secreted netrins, draxin and cerebellins are also ligands for DCC (Ahmed et al 2011;Wei et al 2012;Haddick et al 2014), and UNC5 homologs bind members of the fibronectin and leucine-rich transmembrane (FLRT) protein families (Yamagishi et al 2011). Additional ligands for neogenin include bone morphogenic proteins (BMPs) and repulsive guidance molecules (RGMs) (Rajagopalan et al 2004;Hagihara et al 2011).…”
Section: Netrins and Their Receptorsmentioning
confidence: 99%